Implementasi Konsep Akuntansi Syariah Dalam Pembangunan Infrastruktur Pada Ekonomi Biru Di Indonesia - Ardila Nasution; Kamilah Kamilah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
There are 514 urban areas in the archipelagic nation of Indonesia (Ministry of Home Affairs, 2016). There are many cities in Indonesia that are able to provide a sense of comfort and security for their residents, this of course has an impact on population growth. However, the amount of waste that can be generated and stored is limited by the carrying capacity of the urban environment. Using the idea of ​​a